Thoracic SMARCA4-deficient undifferentiated tumor: A case report in a 40-year-old male without a smoking history - Karnik Soghomonian; Ahmad Ibrahim (SAGE Open Medical Case Reports)
Thoracic SMARCA4-deficient undifferentiated tumor is a recently identified aggressive malignancy characterized by inactivating mutations leading to the loss of SMARCA4 protein expression. First classified in the 2021 World Health Organization Classification of Thoracic Tumors, thoracic SMARCA4-deficient undifferentiated tumor typically presents in men in their fourth to sixth decade of life, often with a history of smoking, though a subset of cases occurs in nonsmokers. We present a rare case of stage IV thoracic SMARCA4-deficient undifferentiated tumor in a 40-year-old male without a smoking history, presenting with spinal metastases. The patient experienced right upper back pain, chest pain, and dyspnea. Imaging revealed a right lung mass, multiple hilar and supraclavicular lymph nodes, and spinal metastases. A computed tomography-guided biopsy of the right lung mass initially suggested small cell carcinoma, but subsequent lymph node excision and expert pathologic review confirmed thoracic SMARCA4-deficient undifferentiated tumor, characterized by rhabdoid morphology and loss of SMARCA4 expression. Treatment included concurrent chemoradiotherapy with cisplatin and etoposide, followed by a regimen of carboplatin, etoposide, and atezolizumab, with maintenance therapy using atezolizumab. Despite complications such as a femoral neck fracture and pancytopenia, imaging showed a reduction in tumor size. This case highlights the diagnostic complexity and treatment approaches for thoracic SMARCA4-deficient undifferentiated tumors.